ENT 530 Social Media Portfolio: Popia Chiz / Hasliza Hassan - Hassan, Hasliza (2020)
POPIA CHIZ is a trademark for our Popia Cheese marketing. The main objective that is to achieve for the business is to offer variety of Popia flavors to our customers with affordable price and luxurious taste flavors. Our business was started on twenty-first of October in 2020. Our product gave a crispiness and fantastic taste because we made it manually and very freshly from the oven make our customer remember the taste. This product is also liked by many people due to cheap and affordable price. Hence, this product provides good insight for the continuation of sale to our customers. The first product that we sold was POPIA CHIZ. After two months of it operation, we launch three new flavors which are POPIA NESTUM, POPIA HORLICKS and POPIA OREO. Since early of its opening, our products received a lot of feedback and encouraging response from the public. Therefore, our business is a good marketable product of choice that can be further expanded to many different areas in future as the business keeps on growing.